Hubungan Pengetahuan Ibu tentang ASI Eksklusif terhadap Pemberian ASI Eksklusif - Elma Monica Putri; Rizki Muji Lestari; Dita Wasthu Prasida (Jurnal Surya Medika (JSM), 2022)
Not giving breastfeeding contributes to infant mortality due to poor nutritional status which affects infant health and infant survival. Monitoring of data on the nutritional status of Indonesia in 2017 showed that the coverage of giving exclusive breastfeeding for the first 6 months by mothers for their infant is still very low at 35.7%. This means there are about 65% of infants are not getting exclusively breastfeeding during the first 6 months of birth. The figure is still far from the coverage of exclusive breastfeeding target in 2019 set by the World Health Organization (WHO) and the Ministry of Health, which is 50%. The aim of this study was to determine the relationship between knowledge about exclusive breastfeeding and exclusive breastfeeding. The research method used in this study is a literature review by analyzing journals about knowledge about exclusive breastfeeding on exclusive breastfeeding from Google Scholar between 2017-2020. The results of the research are there 5 journals stating that there was a relationship between knowledge against giving exclusive breastfeeding with p-value < 0.05 and 1 journal that had no knowledge relationship against giving exclusive breastfeeding with p-value > 0.05. The results of knowledge research are closely related to exclusive breastfeeding. The existence of breastfeeding counselors for mothers during pregnancy can help increase the knowledge of exclusive breastfeeding mothers.